2017
DOI: 10.1590/2177-9465-ean-2017-0110
|View full text |Cite
|
Sign up to set email alerts
|

Physical activities practicing among scholar professors: focus on their quality of life

Abstract: Objective: To investigate the practice of physical activity among scholar professors focusing on their quality of life. Methods:A cross-sectional study was carried out with 121 professors at one of the campuses of a state university in the State of Paraná, using a questionnaire created by Baecke and adapted for the study. Estudio transversal, realizado con 121 docentes, en uno de los campus de una universidad estadual del Estado de Paraná, en el que se utilizó un cuestionario creado por Baecke, adaptado para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…The literature highlights the importance of practicing physical activities as a prevention measure against CMD (Rocha et al, 2012). The encouragement of physical exercises and campaigns for lifestyle change must occur in the university environment because the faculty members tend to spend a large part of their day in hypokinetic activities, including the use of computers, which may favor sedentariness and the presence of anxious symptoms (Dias et al, 2017). Moreover, the practice of physical activities positively influences the life quality of the faculty members (Dumith, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature highlights the importance of practicing physical activities as a prevention measure against CMD (Rocha et al, 2012). The encouragement of physical exercises and campaigns for lifestyle change must occur in the university environment because the faculty members tend to spend a large part of their day in hypokinetic activities, including the use of computers, which may favor sedentariness and the presence of anxious symptoms (Dias et al, 2017). Moreover, the practice of physical activities positively influences the life quality of the faculty members (Dumith, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mental health in the research environment, a study has identified that a large part of university employees consider their work stressful, with higher stress levels being recorded in these professionals compared to workers in general (Guthrie et al, 2017). Also, productivism in the academic environment contributes to faculty members sickness in various ways, with the manifestation of psychosomatic conditions, psychic pathologies, and physical symptoms (Dias et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,26 Em relação à NAF dos participantes, a maioria foi considerada ativa (44,12%), porém, o número de participantes classificados como insuficientemente ativos (10,29%) e sedentários (23,53%) foi elevado, apresentando assim uma preocupação com esse cenário. Estudos com docentes demonstram que esses profissionais tendem à NAF irregulares e inadequados, 26,25,27,28,29 sendo a falta de tempo a justificativa mais utilizada para a pouca prática AF. 30 O contexto da prática de AF insuficiente contribui para o quadro de estresse dos docentes, pois é sabido que a prática de AF tem impacto positivo na saúde e na manutenção e recuperação de condições patológicas de uma população, relacionando-se à diminuição do EP, aumento da qualidade de vida, prevenção e tratamento de doenças degenerativas não transmissíveis, como as cardiovasculares citadas na introdução, por exemplo.…”
Section: Discussionunclassified
“…O sistema de valores e o contexto cultural que determinam a qualidade de vida podem ser identificados nas representações dos entrevistados, que atribuem à qualidade de vida tanto aspectos relacionados à saúde e bem-estar físico expresso no corpo, como aspectos subjetivos que permitem às pessoas "fazer o que se quer" e "ser feliz". Ter um estilo de vida saudável faz parte da representação das pessoas sobre saúde (MARQUES et al, 2017) e está associado à qualidade de vida (DIAS et al, 2017).…”
Section: Ter Saúde é Poder Viver Bem a Vida Sem Se Sentir Doenteunclassified